Detection of colistin resistance in Escherichia coli using the MALDI Biotyper Sirius mass spectrometry system - Furniss,C; Dortet,L; Bolland,W; drews,O; sparbier,K; bonnin,R; Filloux,A; kostrzewa,M; Mavridou,D; Larrouy-Maumus,G (Journal of Clinical Microbiology, 2019)
Polymyxin antibiotics are a last-line treatment for multidrug-resistant Gram-negative bacteria. However, the emergence of colistin resistance, including the spread of mobile mcr genes, necessitates the development of improved diagnostics for the detection of colistin-resistant organisms in hospital settings. The recently developed MALDIxin test enables detection of colistin resistance by MALDI-TOF mass spectrometry in less than 15 minutes, but is not optimized for the mass spectrometers commonly found in clinical microbiology laboratories. In this study, we adapted the MALDIxin test for the MALDI Biotyper Sirius MALDI-TOF mass spectrometry system (Bruker Daltonics). We optimized the sample preparation protocol using a set of 6 MCR-expressing Escherichia coli clones and validated the assay with a collection of 40 E. coli clinical isolates, including 19 confirmed MCR producers, 12 colistin-resistant isolates which tested negative for commonly encountered mcr genes (i.e. likely chromosomally-resistant isolates) and 9 polymyxin-susceptible isolates. We calculated Polymyxin resistance ratio (PRR) values from the acquired spectra; a PRR value of zero, indicating polymyxin susceptibility, was obtained for all colistin-susceptible E. coli isolates, whereas positive PRR values, indicating resistance to polymyxins, were obtained for all resistant strains independent of the genetic basis of resistance. Thus, we report a preliminary feasibility study showing that an optimized version of the MALDIxin test, adapted for the routine MALDI Biotyper Sirius, provides an unbiased, fast, reliable, cost-effective and high-throughput way of detecting colistin resistance in clinical E. coli isolates.